Bekerja dari rumah: implementasinya pada U-Learning selama pandemi virus Covid-19 - Dianawati Suryaningtyas (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
Work from home becomes a solution in Covid-19 pandemic condition. This research aims to explore work from home through U-Learning implementation which is done by lecturers from management and informatics in a private university in Malang. The method used was a qualitative case study with 11 participants who were reached by WhatsApp and returned completed answers of written interviews and photos. All participants implemented U-Learning using the Google Classroom application, while 2 participants added Zoom and Whatsapp applications. Some participants provided a room as a specific place for working from home. Meanwhile, others provided pleasant places in their home to do working although some disturbances from families still happened. Almost all participants felt the benefit of working from home, such as being closer to family and flexibility in time management between working and family, so as to achieve balance. Despite this, participants could not optimize the process of U-Learning caused by technical aspects and also family activities. The limitation of this study is using 11 participants only. For future research suggested using more participants and another method to a better results.